Public attitudes towards COVID-19 vaccine mandates and vaccine certificates in Canada: a time series study - Zhu, David T.; Hawken, Steven; Serhan, Mohamed; Graves, Frank; Smith, Jeff; Wilson, Kumanan (Université d'Ottawa | University of Ottawa, 2024)
Abstract Introduction Since the beginning of the pandemic, numerous public health measures such as COVID-19 vaccines, vaccine mandates and vaccination certificates have been introduced to mitigate the spread of COVID-19. Public opinion and attitudes towards these measures have fluctuated in response to the dynamic political, social, and cultural landscape of the pandemic. Methods We conducted a time-series study consisting of national cross-sectional surveys between November 2021 to March 2022 to evaluate the Canadian public’s attitudes towards COVID-19 vaccine mandates and vaccine certificates. Results When examining public sentiment towards COVID-19 vaccine certificates and proof of vaccination measures, there was a shift in responses over time. The proportion of participants “strongly supporting” these measures decreased from 66.0 to 43.1% between W25(Capacity Limits), −W32 (Mask Mandate Removed), whereas “strongly oppose” was the second most common response and rose from 15.9 to 20.6% during this same time period. Concurrently, when examining participants views surrounding mandates, many participants believed that their province was reopening at “about the right pace”, which remained relatively stable over time (33.0–35.4%) between W28 (Emergency Act)–W32 (Mask Mandate Removed). Conclusion Our study’s findings on the public’s attitudes towards COVID-19 vaccine mandates and vaccine certificates in Canada may aid to guide and streamline the implementation of future similar public health interventions. Future research should include extended follow-up and a more comprehensive examination of trust in government institutions and polarized perspectives on vaccine mandates.